2005
DOI: 10.1109/tasc.2005.848679
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Local Dissipation and Magnetic Field in YBCO Films With Artificial Defects

Abstract: Index Terms-High-temperature superconductors, laser applications, local electric field, local magnetic field, low temperature scanning laser microscopy, magneto optical imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…An earlier paper by Abraimov et al [14] shows that the strong dissipation is observed where the cross sectional area of current transport is reduced and the local current density is high in an epitaxial YBCO film on SrTiO3 substrate. In the fishnet pattern striated CC sample studied, we also find that the increased local current density is the most important factor in the dissipation.…”
Section: Resultsmentioning
confidence: 97%
“…An earlier paper by Abraimov et al [14] shows that the strong dissipation is observed where the cross sectional area of current transport is reduced and the local current density is high in an epitaxial YBCO film on SrTiO3 substrate. In the fishnet pattern striated CC sample studied, we also find that the increased local current density is the most important factor in the dissipation.…”
Section: Resultsmentioning
confidence: 97%
“…Local transport J c measurement using LTSLM The low temperature scanning laser microscope (LTSLM) is a hot spot probe technique [16,[18][19][20] which utilizes a focused probe laser beam to scan the sample surface to induce local temperature perturbations while the voltage change δV responses across the sample are recorded as a function of scan position (x,y). The spatially resolved δV(x,y) responses reflect the local property variation of the superconductor samples.…”
Section: Patterning Of Single Gb Tracksmentioning
confidence: 99%
“…The spatially resolved δV(x,y) responses reflect the local property variation of the superconductor samples. Detailed descriptions of the principles of LTSLM and our setup can be found in [16,21]. Here we focus on two applications of LTSLM that are relevant to this study, the measurement of local J c at T<T c and visualization of the local grain orientation by measurement of thermoelectric power at room temperature.…”
Section: Patterning Of Single Gb Tracksmentioning
confidence: 99%
See 1 more Smart Citation
“…By displacing the laser beam along the stripe we obtain a voltage signal that is modulated by the temperature distribution due to the external thermal effects. The similar laser induced hot spot scanning method is used for investigation of spatial distribution of superconducting parameters and defects visualization [6][7].…”
Section: Introductionmentioning
confidence: 99%